Anti-pentraxin 3 auto-antibodies might be protective in lupus nephritis: a large cohort study. (1st January 2017) - Yuan, Mo; Tan, Ying; Pang, Yun; Li, Yong-zhe; Song, Yan; Yu, Feng; Zhao, Ming-hui
Abstract: Objectives: Anti-pentraxin 3 (PTX3) auto-antibodies were found to be associated with the absence of renal involvement in systemic lupus erythematosus (SLE). This study is to investigate the prevalence of anti-PTX3 auto-antibodies and their clinical significance based on a large Chinese lupus nephritis cohort. Methods: One hundred and ninety-six active lupus nephritis patients, 150 SLE patients without clinical renal involvement, and 100 healthy controls were enrolled. Serum anti-PTX3 auto-antibodies and PTX3 levels were screened by enzyme-linked immunosorbent assay (ELISA). The associations between anti-PTX3 auto-antibodies and clinicopathological parameters in lupus nephritis were further analyzed. Results: Anti-PTX3 auto-antibodies were less prevalent in active lupus nephritis patients compared with SLE without renal involvement (19.4% (38/196) versus 40.7% (61/150), p  < .001). The serum levels of anti-PTX3 auto-antibodies were negatively correlated with proteinuria in lupus nephritis ( r  = −.143, p  = .047). The levels of proteinuria, serum creatinine, and the prevalence of thrombotic microangiopathy were significantly higher in patients with higher PTX3 levels (≥3.207 ng/ml) and without anti-PTX3 auto-antibodies compared with patients with lower PTX3 levels (<3.207 ng/ml) and with anti-PTX3 auto-antibodies (4.79 (3.39–8.28) versus 3.95 (1.78–7.0), p  = .03; 168.84 ± 153.63 versus 101.44 ± 47.36, p  = .01; 34.1% (14/41) versus 0% (0/9), p  = .04; respectively). Conclusion: Anti-PTX3 auto-antibodies were less prevalent in active lupus nephritis patients compared with SLE without renal involvement and associated with less severe renal damage, especially with the combined evaluation of serum PTX3 levels.